Prevalence of nontuberculous mycobacteria in a tertiary hospital in Beijing, China, January 2013 to December 2018 - Huang, Jing-jing; Li, Ying-xing; Zhao, Ying; Yang, Wen-hang; Xiao, Meng; Kudinha, Timothy; Xu, Ying-chun (BMC microbiology, 2020)
To investigate the species distribution of non-tuberculous mycobacteria (NTM) among tuberculosis (TB) specimens collected from January 2013 to December 2018 at Peking Union Medical Hospital (Beijing), China. NTM species identification was carried out by DNA microarray chip. Mycobacterial species were detected in 1514 specimens from 1508 patients, among which NTM accounted for 37.3% (565/1514), increasing from a proportion of 15.6% in 2013 to 46.1% in 2018 (P < 0.001). Among the 565 NTM positive specimens, the majority (55.2%) were from female patients. Furthermore, patients aged 45-65 years accounted for 49.6% of the total patients tested. Among 223 NTM positive specimens characterized further, the majority (86.2%) were from respiratory tract, whilst 3.6 and 3.1% were from lymph nodes and pus, respectively. Mycobacterium intracellulare (31.8%) and Mycobacterium chelonae / Mycobacterium abscessus (21.5%) were the most frequently detected species, followed by M. avium (13.5%), M. gordonae (11.7%), M. kansasii (7.6%), and others. The proportion of NTM among mycobacterial species detected in a tertiary hospital in Beijing, China, increased rapidly from year 2013 to 2018. Middle-aged patients are more likely to be infected with NTM, especially females. Mycobacterium intracellulare and Mycobacterium chelonae/ Mycobacterium abscessus were the most frequently detected NTM pathogens. Accurate and timely identification of NTM is important for diagnosis and treatment.